Economic and Cultural Development: Empirical Studies of Micro-level Data - Lena Lindbjerg Sperling (Copenhagen Business School (CBS), 2019)
What a ects the economic and cultural development tracks of societies? We know that large events such as political changes, natural disasters and migration can change a society dramatically at the macro level, but what exactly happens at the individual level? When conditions change, people are likely to change accordingly both in terms of economic be- havior and cultural values. In this PhD dissertation I explore the underlying developments that occur due to large scale events. The method involves empirical analysis of micro-level cross-sectional data using a rich set of survey data, where the settings progress from state, to country, to the entire world. When looking at individuals within a country, it is possible to tease out the causal e ect of an event a ecting only a share of the individuals who are likely to have otherwise experienced unchanged behavior. My dissertation consists of three sepa- rate articles, each exploring distinct matters but using similar methodological frameworks and econometric techniques. The rst two chapters aim to determine the causal e ect of an event. In the third chapter, we instead describe developments at the global level, adding to knowledge on recent cultural changes. Below, I brie y introduce each paper.
hdl:10398/9725
Keywords: 650